2010
DOI: 10.2320/matertrans.m2009241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grain Size on Hydrogen Environment Embrittlement of High Strength Low Alloy Steel in 45 MPa Gaseous Hydrogen

Abstract: The effect of grain size on the susceptibility of high-strength low alloy steels to hydrogen environment embrittlement in a 45 MPa gaseous hydrogen atmosphere was examined in term of the hydrogen content penetrating the specimen during the deformation. Notch tensile tests were performed in a 45 MPa hydrogen environment using specimens with different prior austenite grain size numbers varying from 2.5 to 5.4. The hydrogen content was measured by thermal desorption analysis with a quadrupole mass spectrometer be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…An initiated crack propagates along the grain boundary if its cohesion is substantially compromised, leading to grain boundary (intergranular) fracture (Figure 1a). This fracture appearance can indeed be observed, particularly after the severe hydrogen charging of martensite with a coarse prior austenite grain structure [14]. Impurities as well as certain alloying elements, e.g., phosphorous and manganese [15][16][17], additionally reduce coherency when segregated to the prior austenite grain boundary, thereby enhancing the deleterious effect of hydrogen.…”
Section: Introductionmentioning
confidence: 94%
“…An initiated crack propagates along the grain boundary if its cohesion is substantially compromised, leading to grain boundary (intergranular) fracture (Figure 1a). This fracture appearance can indeed be observed, particularly after the severe hydrogen charging of martensite with a coarse prior austenite grain structure [14]. Impurities as well as certain alloying elements, e.g., phosphorous and manganese [15][16][17], additionally reduce coherency when segregated to the prior austenite grain boundary, thereby enhancing the deleterious effect of hydrogen.…”
Section: Introductionmentioning
confidence: 94%
“…Takasawa et al 67 reported improved HSC resistance with decreasing prior austenite grain size (PAGS), while Asahi et al 68 and Asahi and Ueno 69 reported improved SSC resistance with refined PAGS, all for QT LAS. A few attempts have been done to investigate the effect of ferrite grain size on HE resistance.…”
Section: Direct and Indirect Effects Of Ni Alloyingmentioning
confidence: 99%
“…Molecular hydrogen is adsorbed onto metal surfaces through physical and chemical adsorption. The molecules then dissociate into atomic hydrogen, which diffuses into the metal body through dislocations at grain boundaries and grains (Takasawa et al, 2010), leading to stress corrosion cracking, hydrogen-induced cracking, hydride cracking and other adverse effects (Okonkwo et al, 2023). These phenomena result in destructive cracks and catastrophic brittle failure of materials sensitive to hydrogen embrittlement (HE).…”
Section: Introductionmentioning
confidence: 99%